Selection of diazotrophic bacteria isolated from wastewater treatment plant sludge at a poultry slaughterhouse for their effect on maize plants - BALDOTTO, LILIAN ESTRELA BORGES (Revista Ceres, 2018)
The economic and environmental costs of nitrogen fertilization have intensified the search for systems that reduce mineral fertilization, for example atmospheric nitrogen-fixing (diazotrophic) bacteria. In this context, the present study addressed: (i) the isolation and quantification of diazotrophic bacteria in the sludge from treated wastewater of a poultry slaughterhouse; (ii) a description of the bacteria, based on cell and colony morphology, and (iii) an assessment of growth and N content of maize plants in response to inoculation. Sixteen morphotypes of bacteria were isolated in six N-free culture media (JMV, JMVL, NFb, JNFb, LGI, and LGI-P). The bacteria stained gram-positive, with 10 rod- and 6 coccoid-shaped isolates. To evaluate the potential of bacteria to promote plant growth, maize seeds were inoculated. The experiment consisted of 17 treatments (control plus 16 bacterial isolates), in a completely randomized design with six replicates. The experimental units consisted of one pot containing two maize plants in a greenhouse. Forty-five days after planting, the variables plant height, leaf number, stem diameter, root and shoot fresh and dry weight, and N content were measured. The highest values were obtained with isolate UFV L-162, which produced 0.68 g total dry matter per plant and raised the N content to 22.14 mg/plant, representing increments of 74% and 133%, respectively, compared with the control. In conclusion, diazotrophs inhabit sludge from treated wastewater of poultry slaughterhouses, and they can potentially be used to stimulate plant development and enrich inoculants.